Profile Measurement Based on Focus Variation Method for Geometrical Defect Evaluation: A Case Study of Cold Forged Propeller Blade. (18th February 2014) - Abdullah, A. B.; Sapuan, S. M.; Samad, Z.
Abstract : Geometrical defect is one of the main problems that will affect performance and perfect mating of produced parts. Coordinate measurement machine (CMM) is commonly used for the measurement, but the use of this machine is limited because of the small size and complexity of the component or features. This study aims to evaluate the defect that occurs on an AA6061 cold forging blade produced using cold forging process based on profile measurement technique. A systematic approach based on focus variation was proposed to evaluate two features, that is, roundness error and twist deviation. The profile was obtained with the use of InfiniteFocus Alicona 3D surface measurement system. Specific algorithms were developed for different cases as the evaluation of the features is discrete and the results were validated.